Early Venous Filling Following Thrombectomy: Association With Hemorrhagic Transformation and Functional Outcome - Elands, Sophie; Casimir, Pierre; Bonnet, Thomas; Mine, Benjamin; Lubicz, Boris; Sjøgård, Martin; Ligot, Noémie; Naeije, Gilles (Frontiers in Neurology, 2021)
Background and Purpose: Previous studies have noted the angiographic appearance of early venous filling (EVF) following recanalisation in acute ischemic stroke. However, its prognostic implications as a novel imaging biomarker remain unclear. We aimed to evaluate the correlation between EVF with (i) the risk of subsequent reperfusion hemorrhage (RPH) and (ii) the impact on the patient’s functional outcome using the NIHSS score at 24hrs and the Modified Rankin Scale (mRS) score at 90 days. Methods: We conducted a retrospective cohort study of patients presenting with an acute ischemic stroke due to a proximal large-vessel occlusion of the anterior circulation treated by thrombectomy. Postreperfusion digital subtraction angiography was reviewed to look for EVF as evidenced by the contrast opacification of any cerebral vein before the late arterial phase. Results: EVF occurred in 22.4% of the 147 cases included. The presence of EVF significantly increased the risk of RPH (p=0.0048), including the risk of symptomatic hemorrhage (p=0.0052). The presence of EVF (p=0.0016) and the absence of RPH (p=0.0021) were independently associated with a better outcome as defined by the NIHSS difference at 24hrs, most significantly in the EVF+RPH- group. No significant relationship was however found between either EVF or RPH and a mRS score ≤ 2 at 90 days. Conclusion: Early venous filling on angiographic imaging is therefore a potential predictor of reperfusion hemorrhage. The absence of subsequent RPH in this sub-group is associated with better outcomes at 24hrs post thrombectomy than in those with RPH.